2023
DOI: 10.18632/aging.204935
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of BACE1 attenuates microglia-induced neuroinflammation after intracerebral hemorrhage by suppressing STAT3 activation

Abstract: Hematoma-induced neuroinflammation is the cause of poor prognosis in intracerebral hemorrhage (ICH); therefore, promoting blood clearance and blocking overactivated inflammation are rational approaches for ICH treatment. β-site amyloid precursor protein (APP) lyase-1 (BACE1) is a key molecule regulating the microglial phenotype transition in neurodegenerative diseases. Therefore, the aim of this study was to investigate the role of BACE1 in microglial phagocytosis and inflammatory features in ICH. Here, we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
(55 reference statements)
0
0
1
Order By: Relevance
“…Previous studies and the current study found that inflammatory and amyloidogenic genes were concomitantly upregulated after LPS treatment (Zhuang et al, 2023). However, PUN has resulted in the inhibition of the expression of the inflammatory mediators such as iNOS, COX2, TNF-ɑ, IL-6, IL-2, and IL-1β as well as ROS in the brain and cells.…”
Section: Discussioncontrasting
confidence: 39%
“…Previous studies and the current study found that inflammatory and amyloidogenic genes were concomitantly upregulated after LPS treatment (Zhuang et al, 2023). However, PUN has resulted in the inhibition of the expression of the inflammatory mediators such as iNOS, COX2, TNF-ɑ, IL-6, IL-2, and IL-1β as well as ROS in the brain and cells.…”
Section: Discussioncontrasting
confidence: 39%